Bone marrow harvesting of allogeneic donors in an outpatient setting: a single-center experience - Kriegsmann, Katharina; Stadtherr, Peter; Bruckner, Thomas; Pavel, Petra; Heilig, Christoph E.; Schmitt, Anita; Puthenparambil, Joe; Brandt, Juliane; Ho, Anthony Dick; Dreger, Peter; Witzens-Harig, Mathias; Wuchter, Patrick (Biology of blood and marrow transplantation, 2016)
The aim of this retrospective study was to assess the safety and efficacy of bone marrow (BM) harvesting of allogeneic donors in an outpatient setting. Data of 226 related and unrelated donors who underwent BM harvest under general anesthesia at our institution from 2002 to 2014 were analyzed. Sixteen patients were a priori planned for admission for social reasons and 210 patients underwent BM harvesting with the intention to perform this procedure on an outpatient basis. To identify factors that predispose for hospital admission, we retrospectively analyzed donor characteristics and collection parameters. Outpatient treatment was performed in 178 of 210 donors (85%), whereas 32 donors (15%) required admission for clinical reasons (mainly clinically relevant anemia and circulatory problems). These individuals were not significantly different in sex distribution, age, donor's body weight, and the proportion of related donors from those who were not admitted. However, we found a significantly higher collection volume per kilogram donor's body weight in inpatients compared with volume for outpatients (16 versus 13 mL/kg body weight, P < .001). Severe adverse events or deaths occurred neither in the inpatient nor in the outpatient setting. Our study demonstrated that BM harvest in an outpatient setting is safe and feasible for the majority of allogeneic donors. A high volume of BM represented a major risk factor for inpatient admission.
Available online 10 November 2015
Gesehen am 28.05.2020